Ochrona dziedzictwa archeologicznego. Wspólne problemy, wspólne obowiązki - Trzciński, Maciej (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
Protection of the Archaeological Heritage is an important and still underrated problem. One of the major problems are still illegal excavations conducted by :"treasure hunters" Monuments stolen in Ukraina, Romania or Bulgaria are trafficked to Central and Western Europe. Take effective and permanent international cooperation seems very urgent to protect archeaological artefacts which are source of European identity.
Keywords: dziedzictwo archeologiczne; ochrona; problemy; obowiązki